Clinicopathological features of paediatric deaths due to myocarditis: an autopsy series. Issue 7 (8th February 2008) - Weber, M A; Ashworth, M T; Risdon, R A; Malone, M; Burch, M; Sebire, N J
Abstract : Introduction: Myocarditis is a recognised cause of cardiac failure in childhood but the frequency of myocarditis as a cause of sudden unexpected death across the paediatric age range is uncertain. Methods: A structured review of the results of all autopsies carried out in a single paediatric centre over a 10-year period, including the results of all investigations performed as part of the centre's policy for the post-mortem investigation of paediatric deaths. Results: During the study period there were 1516 autopsies of children aged 0–18 years. Histologically proven myocarditis was present in 28 cases (1.8%, age range 10 days to 16 years, median age 10 months), of which 16 (57%) presented as sudden death. More than half of all cases (54%) occurred in infants less than 1 year of age, accounting for 2% of infant deaths referred for autopsy, compared with around 5% of childhood deaths over the age of 5 years. In almost 40% of cases there were no macroscopic cardiac abnormalities, the diagnosis being entirely dependent on routine histological examination of the heart, and post-mortem heart weight was normal in the majority of cases. Virus was detected in nine (36%) of the 25 cases in whom virological analyses were performed. The histological features were similar in all cases, with an interstitial inflammatory cell infiltrate, predominantly lymphocytic, with focal myocyte necrosis and interstitial oedema. Conclusions: Myocarditis is a rare cause of death in infancy and childhood, and the majority of cases present as sudden unexpected deaths, which require routine histological sampling of the heart for its detection.